2006
DOI: 10.1091/mbc.e06-04-0355
|View full text |Cite
|
Sign up to set email alerts
|

QKI Binds MAP1B mRNA and Enhances MAP1B Expression during Oligodendrocyte Development

Abstract: Microtubule-associated protein 1B (MAP1B) is essential for neural development. Besides the abundant expression in neurons, MAP1B recently was found in myelinating oligodendroglia. Moreover, MAP1B deficiency causes delayed myelin development, suggesting the functional importance of MAP1B in oligodendroglia. However, molecular mechanisms that control MAP1B expression in oligodendroglia remain elusive. We report here that MAP1B mRNA is markedly upregulated in the oligodendroglia cell line CG4 upon induced differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 44 publications
2
73
1
Order By: Relevance
“…It has been found to regulate multiple posttranscriptional processes, including premRNA splicing, mRNA localization, mRNA stability, and protein translation (43)(44)(45)(46)(47)(48)(49)(50). There are three major isoforms of QKI due to AS, QKI-5, QKI-6, and QKI-7 (51,52).…”
Section: Comprehensive Determination Of Changes In As During Emtmentioning
confidence: 99%
“…It has been found to regulate multiple posttranscriptional processes, including premRNA splicing, mRNA localization, mRNA stability, and protein translation (43)(44)(45)(46)(47)(48)(49)(50). There are three major isoforms of QKI due to AS, QKI-5, QKI-6, and QKI-7 (51,52).…”
Section: Comprehensive Determination Of Changes In As During Emtmentioning
confidence: 99%
“…Indeed, forced expression of QKI-6 and -7 can enhance p27Kip1 expression by stabilization of the p27Kip1 mRNA and promote oligodendrocyte differentiation (Larocque et al, 2005). In addition, our recent studies identified microtubule associated protein 1B mRNA, a key protein regulating oligodendroglia processes extension (Vouyiouklis and Brophy, 1993), as a target of QKI (Zhao et al, 2006). Whether QKI deficiency indeed attenuates oligodendrocyte differentiation in the qk v mutant brain, and furthermore whether the QKI-6 transgene may promote oligodendrocyte differentiation before myelination, are important questions to be addressed by future studies.…”
mentioning
confidence: 97%
“…Using an autosomal recessive mutant (qkv) model, the dysfunction of the mouse QKI gene has been well described as related to body tremor and the severe demyelination of the central nervous system [25]. To date, an increasing number of studies have confirmed that the human QKI gene in the brain plays a fundamental role in myelination and ODC differentiation [26,27]. Abnormal QKI expression may be critical in influencing other myelin-associated gene expression abnormalities in psychiatric disorders, such as schizophrenia and MDD.…”
Section: Discussionmentioning
confidence: 99%